Estudio de alternativas de manejo para la declaratoria de área municipal protegida en el Cerro Putzalahua cantón Latacunga provincia de Cotopaxi - Iturralde Ayala, Daniel Enrique (2015)
This research is the process result for the management plan construction for the area of Putzalahua volcanic extract, managed by private initiatives between researchers from the Technical University of Cotopaxi and the Municipal Government of Latacunga Canton, through the services processing provision. The study includes a brief characterization of biophysical, socioeconomic and potential projects for the area aspects; allowing to know the current situation and the possibilities of management; Additional recommendations are set to define workable for protecting the study area alternatives. "The study area includes 52 km east of Latacunga Canton, specifically in the Belisario Quevedo parish. Grassland, wetland, forest, 4 living areas were identified. On checking component plant species 27 native species of mountain center features identified. 19 fauna species including birds, mammals, insects, reptiles and amphibians that their special characteristics as species of flora are listed in the Red Book of species were identified.